Case Study Of Logistics And Supply Chain : Ato Fina (Guangzhou) Chemicals Co., Ltd. - Hao, Wang (2008)
This case study describes the operation system of opacifier product in AtoFina (Guangzhou) Chemicals Co., Ltd. and analyzes the current situation of the company\'s supply chain management of the product with the theory of supply chain managemnet and brings forth suggestion on further improvement in hope of serving reference for the company or similar companies.